Medical Students’ Assessment of Eduard Pernkopf’s Atlas: Topographical Anatomy of Man - Coombs, Demetrius M.; Peitzman, Steven J. (Annals of anatomy, 2017)
To date, there has been no study examining the perceptions of first-year medical students regarding Eduard Pernkopf’s atlas, particularly during their study of gross anatomy and prior to coursework in medical ethics. We present a discussion of Pernkopf’s Atlas: Topographical Anatomy of Man from the perspective of U.S. medical students, and sought to determine whether medical students view Pernkopf’s Topographical Anatomy of Man as a resource of greater accuracy, detail, and potential educational utility as compared to Netter’s Atlas of Human Anatomy. The entire first-year class at Drexel University College of Medicine (265 students) was surveyed at approximately the midpoint of their gross anatomy course and 192 responses were collected (72% response rate). Of these, 176 (95%) were unaware of the existence of Pernkopf’s atlas. Another 71% of students found the Pernkopf atlas more likely complete and accurate, whereas 76% thought the Netter atlas more useful for learning (p<.001). When presented with a hypothetical scenario in which the subjects used in creating Pernkopf’s atlas were donated, or unclaimed, but with knowledge that Pernkopf was an active member of the Nazi party, 133 students (72%) retained their original position (p=.001). About 94% desired discussion of Pernkopf within a medical school bioethics course. The relationship between level of self-reported knowledge and whether or not students would advocate removal of the atlas was statistically significant (p=.013). Discussing ethical violations in medical history, especially the Pernkopf atlas, must attain a secure place in medical school curricula, and more specifically, within a bioethics course.